Insight into cations substitution on structural and electrochemical properties of nanostructured Li2FeSiO4/C cathodes. Issue 3 (18th October 2019) - Sivaraj, Pazhaniswamy; Abhilash, Karuthedath Parameswaran; Nalini, Balakrishnan; Selvin, Paneerselvam Christopher; Goel, Sunkulp; Yadav, Sudheer Kumar
Abstract: Structural instability is the major obstacle in the Li2 FeSiO4 /C cathode during charge and discharge process, which can be improved by the substitution of cations in the host cage. In this study, the transition metal ions with different valence (Ag 1+, Zn 2+, Cr 3+, and Ti 4+ ) have been substituted in Li2 FeSiO4 /C via modified sol‐gel method and the impact on the structural, electrical, and electrochemical performances has been systematically explored. The Rietveld‐refined XRD pattern and HR‐TEM (SAED) result reveal that all the prepared samples maintain orthorhombic structure (S.G‐ Pmn 21 ). The FE‐SEM and TEM micrographs of bare and doped Li2 FeSiO4 /C display nanoparticle formation with 20‐40 nm size. Among different cation‐substituted silicates, Li2 Fe0.9 Ti0.1 SiO4 /C sample exhibits an excellent total conductivity of 1.20 × 10 −4 S cm −1 which is one order of magnitude higher than the bare Li2 FeSiO4 /C sample. The galvanostatic charge‐discharge curves and cyclic voltammetric analysis reveal that the Li2 Fe0.9 Ti0.1 SiO4 /C material provides an excellent initial specific capacity of 242 mAh g −1 and maintains a capacity of 226 mAh g −1 after 50 cycles with capacity retention of 93.38%. The Ti doping is a promising strategy to overcome the capacity fading issues, by preventing the structural collapse during Li‐ion intercalation/de‐intercalation processes in the Li2 FeSiO4 /C electrode through the strong hybridization between the 3 d and 4 s orbitals in titanium and 2 p orbital in oxygen. Abstract : Effect of cation doping on structural and electrochemical perfomance of nanostructured‐Lithium iron silicate.